The Role of Soft Power in Arab Union Education Diplomacy in Indonesia (Case Study of Alef Education Platform) - Khoirunnisa, Khoirunnisa; Nurwahidin, Nurwahidin (Journal of Social Science, 2024)
Educational diplomacy has become an important element in international relations, especially in the era of globalization and technological revolution. This research aims to explore the role of United Arab Emirates (UAE) soft power in education diplomacy in Indonesia, particularly in the context of technology transfer and innovation. Using a descriptive-analytical qualitative approach, this research examines the dynamics of bilateral relations between the UAE and Indonesia, through technology-based education initiatives, such as the Alef Education platform. The results show that the United Arab Emirates has utilized various tools in education diplomacy, including technology transfer in Indonesia through Alef Education, proven to improve accessibility and quality of learning in Indonesia. However, the research also found challenges, including cultural differences, regulatory barriers, and limited technology-based education infrastructure, as well as program synergies with the national curriculum to support the sustainability of these programs. This research provides a deep insight into how the UAE's education diplomacy becomes a strategic tool in strengthening bilateral relations and creating long-term impact for Indonesia's education sector. The implications of this research can help identify opportunities for further cooperation in the field of education technology and innovation